SISTEM REKRUTMEN DAN SELEKSI, PENEMPATAN TENAGA PENDIDIK DI SMP ISLAM DARUL HIKMAH MAKASSAR - Suriadin Suriadin (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2019)
Recruitment and Placement System Educators are one of the most important elements in improving the quality of education. Educators are members of the community who are devoted and appointed to support the implementation of education, which includes education unit managers, overseers, study tutors, supervisors, researchers, developers, librarians, laboratory assistants and learning resource technicians. One of the problems that often occurs in the recruitment and placement of teaching staff is the problem of less mature recruitment planning so that there is often a failure in achieving school objectives because many work that must be done by several people must be done alone. This usually occurs because of the lack of experts in certain fields of work.